Approximation numbers of Sobolev embeddings of radial functions on isotropic manifolds - Leszek Skrzypczak; Bernadeta Tomasz (Journal of Function Spaces and Applications)
We regard the compact Sobolev embeddings between Besov and Sobolev spaces of radial functions on noncompact symmetric spaces of rank one. The asymptotic formula for the behaviour of approximation numbers of these embeddings is described.